Common teaching strategies in aimara rural schools - Sosa Gutierrez, Fredy (2021)
The research work describes and analyzes the teaching-learning strategies used by the teachers of the rural Yaputira - Huancané 2019 school, this reveals the teaching strategies most used by teachers in Aymara secondary schools. The work corresponds to the quantitative approach, being its descriptive transectional design. In its development, a survey was applied to all students, in which they reported, regarding the recurrent teaching strategies by the teacher. The statistic used was the statistical package SPSS Statistics 25, in which it was determined that 59.4% teachers are located on the scale of almost always using strategies to inquire about knowledge, 43.75% are located on the scale sometimes make use of Of the strategies that promote the organization of information and 46.9% are located on the scale, they sometimes use group strategies. This means that students point out that their teachers rarely use these types of strategies in the teaching-learning process. At the same time, it shows a necessary improvement in initial teacher training, on the other hand, weak assistance in the processes of monitoring and accompaniment of the intermediate decentralized management bodies of the Ministry of Education.